Ventanillas de Salud (VDS) and Mobile Health Units (MHU): A binational collaborative models - Rangel Gómez, María Gudelia; Salazar, Saúl; López Jaramillo, Ana María; Lira Chávez, Isaura Angélica; Romero Rangel, Alejandra; Caballero Abraham, Martha Leticia; Gutiérrez Reyes, Luis; Rosales, Cecilia B. (Frontiers in Public Health, 2022)
Over the years, the Mexican population in the United States has faced high prevalence of health-related inequalities and disadvantages and represents one of the most vulnerable migrant groups in the country. To help reduce the gaps in health care for the Mexican population, the Mexican government, in collaboration with strategic allies from various sectors, launched the Ventanillas de Salud (VDS) strategy, which was subsequently reinforced through the Mobile Health Units (MHU) care model. Both the VDS strategy and the MHU care model are intended to contribute to the development of initiatives, projects, and actions in health that will benefit the Mexican community living in the United States, which lacks or has difficulty accessing health services. This article provides a descriptive, analytical analysis of the VDS strategy and the MHU care model, as unique collaborative models, which can be replicated, and have achieved a positive impact on the health of Mexican and other Hispanic communities in the United States, at both the individual and community level.